2020
DOI: 10.1080/19475705.2020.1836040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multi-GNSS high-rate relative positioning for monitoring dynamic structural movements in the urban environment

Abstract: Skyscrapers cause both limited sky-view and multipath error when using Global Navigation Satellite System (GNSS) measurements for monitoring structural movements. To reduce multipath errors, cutoff elevation angle can be set to a high value such as 30 À40. However, in the case of employing high cutoff elevation angles, the use of GPS only may not provide adequate positioning solutions. To overcome this problem, Galileo and GLONASS observations are combined with GPS observations. This study experimentally inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It can be observed that satellite selection becomes more challenging due to the size of the satellite subset, requiring higher parameter values and longer computation time. ABC showed better accuracy in selecting the optimum four GNSS satellite subset compared to the other sizes of satellite constellations (8,12,15) using the first two cases of parameter settings. This is due to the significant increase in the possible satellite combinations, which follows the increase in the number of satellites in the constellation (from 4 to 8, 12, and 15) (Figure 10).…”
Section: Multi-gnss Optimal Satellitesmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be observed that satellite selection becomes more challenging due to the size of the satellite subset, requiring higher parameter values and longer computation time. ABC showed better accuracy in selecting the optimum four GNSS satellite subset compared to the other sizes of satellite constellations (8,12,15) using the first two cases of parameter settings. This is due to the significant increase in the possible satellite combinations, which follows the increase in the number of satellites in the constellation (from 4 to 8, 12, and 15) (Figure 10).…”
Section: Multi-gnss Optimal Satellitesmentioning
confidence: 98%
“…GNSS satellite selection is the process of choosing the right GNSS satellite combination from the available GNSS satellites, aiming for better positioning quality with a lower computational load [10]. Various satellite selection criteria have been used for selecting satellites, including satellite elevation angle [11][12][13], satellite signal quality [14,15], GDOP [3,16,17], and weighted GDOP (WGDOP) [18,19]. Since GNSS accuracy is affected by both satellite geometry (i.e., GDOP) and satellite signal quality, the WGDOP, which is based on the satellite signal quality and the satellite geometry (GDOP), can be considered as the most suitable criterion for choosing satellites.…”
Section: Introductionmentioning
confidence: 99%
“…High-precision 3D position information from GNSS data plays an important role in detecting dynamic behavior on the fault [21]. In addition to GNSS seismology, many scientific studies have been carried out by integrating GNSS sensors in areas such as structural health monitoring for the detection of damage to buildings during earthquakes, early warning systems for the pre-detection of natural disasters such as earthquakes or tsunamis [22][23][24][25][26][27][28][29][30]. As a result of the northward movement of the Arabian Plate in the southeast of the East Anatolian Fault and the westward movement of the Anatolian Plate in the northwest, the studies carried out on this fault at different times are approximately 9±1mm/year [31], 5-8mm/ year [32,33], 10mm/year [4,34], 13mm/year [35], 11±3mm/year and 8mm/year [36], slip rates were calculated.…”
Section: International Journal Of Environmental Sciences and Natural ...mentioning
confidence: 99%
“…Compared to geotechnical sensors such as accelerometers, the high-rate GNSS technique can directly detect displacements in the terrestrial reference frame, free of clipping or errors caused by integration or saturation [3]. It is worth mentioning here that the applications of detecting dynamic displacements in RT have been dominated by the RT kinematics (RTK) technique for almost two decades due to the high accuracy it provides [4][5][6]. However, the RTK technique requires an external GNSS infrastructure to ensure high accuracy, which will unavoidably render it unusable in the event of a possible mega-earthquake [7].…”
Section: Introductionmentioning
confidence: 99%